Democratic Republic of the Congo : Staff Report for the 2003 Article IV Consultation, First Review Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2003)
This paper examines the Democratic Republic of the Congo's 2003 Article IV Consultation, First Review Under the Poverty Reduction and Growth Facility (PRGF), and Request for Waiver of Performance Criteria. Through September 2002, overall performance under the PRGF-supported program was broadly satisfactory, with good progress in the structural area. The annualized rate of inflation for the first nine months of 2002 reached 11 percent, down from 135 percent in 2001. Economic growth is expected to be positive for the first time in 13 years.